Novos mundos possíveis : o canto coral como arte e resistência - Paro, Elizabete Angela (2015)
This work approaches the choir practice, as from contemporary cultural theories, in Brazilian groups that stood out for its non-alignment to the hegemony, and also by my own experience as a conductor. The theoretical support is based on Guattari, about subjectivity and singularity processes; Rancière, art and resistance; Bourdieu, the construction of taste; Quijano and Mignolo, Decoloniality. Two choral performances were analyzed, in dialogue with theories presented, considering extra-musical issues.